Seed quality deterioration due to temporal variation of biotic and abiotic factors in cucumber (Bangladesh Journal of Agricultural Research, 2009)
Cucumber seeds were taken to assess the effect of temporal variation on the seed quality. Seeds were stored in three types of containers, such as metal (tin), polythene bag, and cloth bag. The containers were stored at room temperature and ambient relative humidity around three months. Seed quality factors viz., moisture content, germination percentage, vigor index, percentage of abnormal seedling, fresh seed, dead seed, hard seed, root-shoot ratio and amount of dry matter were recorded every 15 days interval. The initial moisture content of seed in tin, poly bag, and cloth bag were 10.66%, 10.13%, and 9.89%, respectively, but it was increased with increasing storage time after 60 days (11.08%, 10.67%, and 10.98%). The germination percentage was higher at 15 days after observation (DAO) for different containers like tin (90%), poly bag (86%), and cloth bag (85%) than after 60 DAO (86%, 84%, and 80%), respectively, on blotting paper substrate. The percentage of dead seed was increased from 2 to 10%, 5 to 12%, and 6 to 12% in tin container, poly bag, and cloth bag, respectively, from 15 DAO to 60 DAO. The vigor indexes of seedling were 14.58, 12.85, and 10.92 at 15 DAO in tin, poly bag, and cloth bag, respectively, which attained at 10.39, 10.26, and 10.08 at 60 DAO, respectively. The length of seedling was 25.85 cm, 25.15 cm, and 24.30 cm at 60 DAO in tin, poly bag, and cloth bag, respectively. Shoot-root ratio was found highest in tin container at 15 DAO (0.95) and lowest in cloth bag (0.70) at 60 DAO. Key Words: Seed quality, cucumber, temporal variation, biotic and abiotic factors. DOI: 10.3329/bjar.v34i3.3972 Bangladesh J. Agril. Res. 34(3) : 457-463, September 2009